Neuroimaging and Electrophysiology Evidence Unveiling the Mystery of Disorders of Consciousness - BAI Yang (康复学报)
As consciousness has always been an unsolved mystery for human beings, the diagnosis and prognosis of disorders of consciousness (DOC) after brain injury have also faced great challenges in clinical practice. Researchers and clinicians have been actively searching for clues from neuroimaging and electrophysiology to explore the biological and pathological mechanisms of human consciousness and to provide new evidence for the neural basis of consciousness impairment and rehabilitation. Among them, neuroimaging techniques, including positron emission tomography (PET), functional magnetic resonance imaging (fMRI), and functional near-infrared spectroscopy (fNIRS), as well as electrophysiological techniques, including spontaneous electroencephalograms (EEG), event-related potentials (ERPs), and transcranial magnetic stimulation-induced electroencephalograms (TMS-EEG), have provided different dimensional features related to consciousness. These techniques have all somewhat advanced the clinical diagnosis and prognosis of DOC, and are closely linked to DOC-related clinical practice, facilitating more scientific clinical management of DOC patients.